(3GdQSGdI GdfadjIs - (3GdYGedj GdfHWj GdLRjfi, TeS GdOjf, GdTgjO GdChd, eMeO Hf eci Hf eMeO Hf MGeO, J (B786 (3g`s ((3jYbhH Hf CUjd GdCHQbhgjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3aEfj deG hbaJ Ydi GdMOjKjf GdeTghQjf Yf Cgd GdHjJ Ydjge GdSdGe GdfHhI CYXe (B... (3CMOgeG Yf GdEeGe GdUGOb CHj YHO Gddg LYaQ Hf eMeO Ydjg hYdi BHGFg hCHfGFg Cced GdJMjGJ (B...s
(3BNQgG (B:s
... (3GaYd Gh dG JaYd aPGc hEf JaQbJ Yed Ydi CcKQ GdNeS hdUdGI GdTcQ GfgG QcYJGf YfO JLQO fYeI Ch OaY fbeI ChaVGA MGLI jbQC aj GdGhdi GdMeO hGdJhMjO haj GdKGfjI GdMeO hGdLMO (B... (3JeJ GdQSGdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGYdGe (B7\109s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis